2013
DOI: 10.1097/wad.0b013e31826d597a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma Proteomic Data for Alzheimer Disease State Classification and for the Prediction of Progression From Mild Cognitive Impairment to Alzheimer Disease

Abstract: Previous studies that have examined the potential for plasma markers to serve as biomarkers for Alzheimer disease (AD) have studied single analytes and focused on the amyloid-β and τ isoforms and have failed to yield conclusive results. In this study, we performed a multivariate analysis of 146 plasma analytes (the Human DiscoveryMAP v 1.0 from Rules-Based Medicine) in 527 subjects with AD, mild cognitive impairment (MCI), or cognitively normal elderly subjects from the Alzheimer's Disease Neuroimaging Initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 53 publications
2
53
0
1
Order By: Relevance
“…The full texts of the remaining 40 publications were assessed for eligibility. A total of 28 studies were included in the qualitative synthesis of which 12 had a prospective study design [14, 16, 18, 19**, 20, 21, 22, 23, 24, 25**, 26, 27] and 16 had a cross-sectional design [28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43]. By hand search of reference lists and recent updates of included studies one additional publication was identified [44].…”
Section: Identification Of Study Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of the remaining 40 publications were assessed for eligibility. A total of 28 studies were included in the qualitative synthesis of which 12 had a prospective study design [14, 16, 18, 19**, 20, 21, 22, 23, 24, 25**, 26, 27] and 16 had a cross-sectional design [28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43]. By hand search of reference lists and recent updates of included studies one additional publication was identified [44].…”
Section: Identification Of Study Reportsmentioning
confidence: 99%
“…The Study of Dementia in Swedish Twins compared the concentration of apoA-I in 23 discordant twin pairs (one twin developed dementia over 3 years, the other does not) and found no difference in apoA-I concentrations [20]. Cross-sectional investigations from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study [45] and another small case-control study from Austria found 1.06 and 1.7 times higher plasma apoA-I concentrations, respectively, in individuals with AD compared with controls [23, 36]. In an age- and sex-matched case-control study, higher apoA-I levels have been associated with prevalent AD [40].…”
Section: New Insights Into the Role Of Hdl-c And Apolipoproteins In Dmentioning
confidence: 99%
“…In the Alzheimer's Disease Neuroimaging Initiative, biomarker panels including NT-proBNP did not distinguish progression from mild cognitive impairment to Alzheimer's disease over 2 years [27]. In 464 Finnish subjects aged 75 and older, higher baseline NT-proBNP was associated with decline in the MMSE score and a 1.53-fold increased risk of dementia (with only 59 cases) over 5 years [28].…”
mentioning
confidence: 99%
“…Five analytes, including apolipoprotein A-II, apolipoprotein E, serum glutamic oxaloacetic transaminase, a-1-microglobulin, and natriuretic peptide, were common to all signatures. Unfortunately, none of these predicted the conversion from MCI to AD [9]. A similar approach was carried out by Soares et al [10], who showed increased plasma levels of eotaxin 3, pancreatic polypeptide, and N-terminal protein B-type brain natriuretic peptide in patients with AD, in line with previous observations in CSF.…”
Section: Clinical Aspects and Biomarkersmentioning
confidence: 68%
“…In an attempt to identify peripheral biomarkers for AD, Llano et al [9] performed a multivariate analysis of 146 plasma analytes in a large cohort of patients with AD or MCI as compared with elderly controls. They identified four different proteomic signatures, each composed of 5-14 analytes that differentiate AD from controls with sensitivity and specificity ranging from 74 to 85 %.…”
Section: Clinical Aspects and Biomarkersmentioning
confidence: 99%